ASSESSING STUDENTS' MASTERY OF TEST OF ENGLISH AS A FOREIGN LANGUAGE - Novita, Dewi (Jurnal Visi Ilmu Pendidikan, 2025)
This study investigates the English proficiency of 117 pre-service teacher students, aged 19 to 21, assessed using the Test of English as a Foreign Language (TOEFL). Focusing on listening comprehension, structure and written expression, and reading comprehension, the research employed descriptive statistics for analysis. The average score was found to be 412, with a range from 370 to 497. Based on the Common European Framework of Reference (CEFR), students were classified within the A2 to B1 proficiency levels, indicating elementary to intermediate skills. Reading and listening comprehension proved to be particularly challenging, with mean scores of 39.3 and 38.7, respectively. Analysis revealed that difficulties primarily arose from struggles with unfamiliar vocabulary, suggesting that limited vocabulary knowledge significantly hindered performance. The findings indicate that identifying specific areas of difficulty can help students focus on essential concepts for improvement in future assessments. Moreover, the study highlights the need for systematically mapping student scores to enhance preparation strategies. These insights provide a clearer understanding of the challenges faced by pre-service teachers in developing their English language skills, leading to recommendations for targeted interventions in their academic training.